2020
DOI: 10.1055/s-0040-1714655
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Incidence and Management of Acute Appendicitis in Children—A Population-Based Study in the Period 2000–2015

Abstract: Introduction Recent studies suggest that the epidemiology and management of appendicitis have changed during the last decades. The purpose of this population-based study was to examine this in the pediatric population in Denmark. Materials and Methods Data were retrieved from the Danish National Patient Registry, the Danish Civil Registration System, and the Statbank Denmark. Patients aged 0 to 17 years diagnosed with appendicitis and appendectomized during the period 2000 to 2015 were included. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
1
9
0
2
Order By: Relevance
“…27 A previous Danish study showed that the normal median therapeutic delay from admission to surgery is 5-7 h for patients with appendicitis. 28 Based on this, it does not seem plausible that the lower incidence of complicated appendicitis in our study was caused by a decreased therapeutic delay from admission to surgery for patients with appendicitis.…”
Section: Discussionmentioning
confidence: 59%
“…27 A previous Danish study showed that the normal median therapeutic delay from admission to surgery is 5-7 h for patients with appendicitis. 28 Based on this, it does not seem plausible that the lower incidence of complicated appendicitis in our study was caused by a decreased therapeutic delay from admission to surgery for patients with appendicitis.…”
Section: Discussionmentioning
confidence: 59%
“…We found a very good PPV for laparoscopic appendectomy of 99% (95% CI, 97%–99%), which has become the dominating surgical approach for both adults 16 and children 17 in Denmark. This is in line with the results of two previous Danish validation studies on the surgical approach for appendectomy.…”
Section: Discussionmentioning
confidence: 78%
“…However, the operative report provides insight into the course of treatment chosen by the operating surgeon. In Denmark, the median length of stay is 16 h and 17 h for adults 16 and children, 17 respectively. Therefore, the histopathology report will not affect the treatment course as this is typically not completed until days after the operation when the patients have already been discharged.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study reports a significant change in the incidence of acute appendicitis including a decline in all age groups except those younger than 5 years. 40 A reliable predictive score for acute appendicitis in children younger than 4 years would help reduce delays in appendicectomy with the associated high risk of appendiceal perforation while reducing the need for invasive diagnostic procedures. 41…”
Section: Discussionmentioning
confidence: 99%